PERAN WISATA BAHARI DALAM MENINGKATKAN PEREKONOMIAN MASYARAKAT DESA KEBOIRENG KECAMATAN BESUKI KABUPATEN TULUNGAGUNG (STUDI KASUS DI OBYEK WISATA PANTAI GEMAH TULUNGAGUNG) - Wilujeng Wulandari (STKIP PGRI Tulungagung, 2022)
AbstractThis study aims to describe: 1) the role of gemah beach tourism objects in increasing local government revenues, 2) the role of gemah beach tourism objects in increasing the income of the surrounding community, 3) obstacles faced by managers in managing Gemah beach attractions. This study uses a qualitative method, so that the data obtained is more complete and more in-depth, the data collection technique is through interviews, namely by question and answer with managers and traders in the Gemah Beach area. Observation, namely through observing and recording the phenomena that are being studied. Documentation, which is a record of events that have passed, can be in the form of images or writing.The results of the study reveal that 1) Gemah Beach tourism object plays an important role in increasing local government revenue even though Gemah Beach tourism object is not the only one that contributes tax retribution because Gemah Beach tourism object attracts a lot of attention from people in the city and outside the city. 2) With the opening of the Gemah Beach tourist attraction, it can increase employment and business opportunities for the people of Keboireng Village. 3) The obstacles faced are ticket purchases which are still done directly which causes congestion when entering the area around Gemah Beach and there is still a lot of garbage strewn about by tourists and garbage from the sea. Keywords: The Role of Maritime Tourism, Keboireng Village Community Income